A novel spirooxazine derivative as a colorimetric probe for Fe2+ and Pb2+ determination on microfluidic paper-based analytical device (μPAD) for maintaining in photochromic efficiency. (December 2022) - Khunkhong, Niyada; Kitchawengkul, Nattasa; Wongnongwa, Yutthana; Jungsuttiwong, Siriporn; Keawin, Tinnagon; Promarak, Vinich; Nalaoh, Phattananawee; Suttisintong, Khomson; Chansaenpak, Kantapat; Jarujamrus, Purim
Abstract: The synthesis of a novel spirooxazine (1-benzyl-3, 3-dimethylspiro[indoline-2, 3′-naphtho [2, 1-b] [1, 4] oxazine, BSP-SP) was developed as a colorimetric probe for the quantitative analysis of Fe 2+ and Pb 2+ in water samples. The device is based on a microfluidic paper-based analytical device (μPAD). BSP-SP was characterized by various techniques, e.g. single-crystal X-ray diffraction (SC-XRD) and time-dependent density functional theory (TD-DFT). In addition, the density functional theory (DFT) allowed us to understand better the adsorption of Fe 2+ and Pb 2+ over other cations adsorption on the BSP-MO structure. The structural isomerization of BSP-SP occurs as an open-form merooxazine (BSP-MO), which acts as a ligand to form Fe 2+ /BSP-MO and Pb 2+ /BSP-MO complexes. We observed these complexes under UV irradiation as having a light blue coloration. The μPADs were also proposed as detection platforms to maintain photostability and photochromic efficiency and extend the lifetime of the spirooxazine. Under optimal conditions, the developed μPAD enables rapid and sensitive quantitative analysis of Fe 2+ at pH 6 and Pb 2+ at pH 11. The limits of detection (LOD) were 0.036 mg L −1 for Fe 2+ and 0.152 mg L −1  Pb 2+ . Overall, the developed sensors, particularly the μPADs, promise the practical analysis of Fe 2+ and Pb 2+ in water samples. Graphical abstract: Image 1 Highlights: Our novel spirooxazine (BSP) was successfully synthesized as colorimetric probe. BSP-coated μPAD was illustrated to enhance photochromic efficiency. This method features selectivity toward Fe 2+ and Pb 2+ determination.